1990
DOI: 10.1295/polymj.22.206
|View full text |Cite
|
Sign up to set email alerts
|

A New Thermo-Sensitive Hydrogel: Poly(ethylene oxide-dimethyl siloxane-ethylene oxide)/Poly(N-isopropyl acrylamide) Interpenetrating Polymer Networks I. Synthesis and Characterization

Abstract: ABSTRACT:Interpenetrating polymer networks (IPNs) composed of poly(ethylene oxidedimethyl siloxane-ethylene oxide) (PEO-PDMS-PEO) ABA triblock copolymer and poly(Nisopropyl acrylamide) (PIPAAm) were synthesized. Transmission electron microscopy (TEM) and differential scanning calorimetry (DSC) studies of bulk IPNs revealed micro phase separation with partial phase mixing between two chemically independent networks. Aqueous equilibrium swelling curves were examined as a function of temperature. DSC thermograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Therefore, enhancing strength and improving response of the hydrogel become a main problem in the expansion of its applications. It is reported that the IPN structure could make up this disadvantage, because this technology can offer the possibility to obtain materials with combined properties of the components, in semiIPNs, one of the two polymers has a linear structure; in IPNs, both polymers have crosslinked structures [8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, enhancing strength and improving response of the hydrogel become a main problem in the expansion of its applications. It is reported that the IPN structure could make up this disadvantage, because this technology can offer the possibility to obtain materials with combined properties of the components, in semiIPNs, one of the two polymers has a linear structure; in IPNs, both polymers have crosslinked structures [8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Variations in these parameters produce interesting structural changes, which could eventually be important for biomedical applications. As thermosensitive hydrogels we can mention N ‐substituted acrylamide derivatives such as poly( N ‐isopropylacrylamide),9–11 poly( N,N ‐diethylacrylamide),12 methylacrylamide,13 partially hydrolysed polyacrylamide,14 agarose15 and poly( N,N ‐diethylacrylamide‐ co ‐ N ‐isopropylacrylamide) 16. Copolymerization of acrylamide with more hydrophilic monomers, such as acrylic acid17 or sodium acrylate,18 has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Copolymerization with a hydrophobic monomer or the formation of an interpenetrating polymer network (IPN) may lead to a higher mechanical strength in comparison with that of a homopolymer network of PNIPA 18–20. Modifications of the PNIPA hydrogel through the formation of an IPN structure have been found to enhance the mechanical properties of the PNIPA hydrogel 19–23. Okano et al21, 22 prepared poly(ethylene oxide‐dimethylsiloxane‐ethylene oxide)/poly( N ‐isopropyl acrylamide) IPN hydrogels and investigated the release behavior of indomethacin and ketoprofen.…”
Section: Introductionmentioning
confidence: 99%